Estrutura da comunidade zooplanctônica na região costeira adjacente à foz do Rio Doce: cenário após o rompimento da barragem de Fundão-MG - Conceição, Laura Rodrigues da (2021)
In the context of environmental impacts generated by the mining activity, which includes the rupture event of the Fundão-MG dam, in addition to considering the ecological importance of the marine zooplankton and the scarcity of studies focused on this problem, this work proposed to identify the impacts in the zooplankton community due to the presence of tailings in the marine area adjacent to the Doce River Mouth, Espírito Santo, Brazil, in addition to characterizing the community structure in relation to the oceanographic structure present in the area. The goals to characterize and evaluate the scenario in the years following the arrival of the tailings sludge (2016/2017/2018), considering a zooplankton community structure; the effects of suspended particulate matter on organisms; the relationship of the community with oceanographic characteristics considering the structuring of water masses and environmental variables (chlorophyll-a and pheopigments). Water samples were collected for analysis and quantification of environmental variables (Niskin and Vandorn bottles were used) and zooplankton (through oblique hauls with a cylindrical-conic plankton net coupled with a flow meter) were collected from fourteen sampling stations for further analysis in the laboratory. Inferential and statistical analyzes (univariate and multivariate) were applied to show the best structure of biotic and abiotic data. The results showed that in the first year after the arrival of the tailings (2016), Copepoda community presented, in general, loss of diversity and abundance when in a scenario of higher values of suspended particulate matter, showing a negative impact due to the presence of tailings associated with them. In the three subsequent years (2016-2018), there was a predominance of certain meroplankton over others (for example, bivalve and ophiuroid larvae) suggesting a possible replacement of dominant groups in the Doce River Mouth. The South Atlantic Central Water proved to be an important factor for the improvement of oceanographic conditions in the study area, especially in scenarios of higher concentration of suspended particulate matter, being responsible for the increase in abundance values and diversity indexes. The analyzes of the functional groups of copepods revealed that associated with the senescent phytoplankton community, there was a predominance of detritivorous and carnivorous organisms. Furthermore, the introduction of a species of non-native Oithonidae copepod (Oithona hamata) was identified in the south of Doce River Mouth, where the main hypothesis is that it was introduced from ballast water. The present work, therefore, brings subsidies that evidence the chronic impact caused by the presence of the tailings, being a relevant reference for future studies to understand the disaster due to the rupture of the Fundão-MG dam in the marine portion adjacent to Doce River Mouth.